2021
DOI: 10.1007/s12551-021-00876-9
|View full text |Cite
|
Sign up to set email alerts
|

Insights into lipid-protein interactions from computer simulations

Abstract: Lipid-protein interactions play an important direct role in the function of many membrane proteins. We argue they are key players in membrane structure, modulate membrane proteins in more subtle ways than direct binding, and are important for understanding the mechanism of classes of hydrophobic drugs. By directly comparing membrane proteins from different families in the same, complex lipid mixture, we found a unique lipid environment for every protein. Extending this work, we identified both differences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…In the last years, the membrane curvature has moved into the focus of membrane protein research (Iversen et al, 2015;Tieleman et al, 2021), one prominent example being the exact arrangement of the ATPases in the tubular cristae of mitochondria (Blum et al, 2019) or the mechanosensitive FIGURE 5 | amplitude histogram is shown in e; in total 5 channels were present in the recording. (E), Current amplitude histograms of KcsA channels in pure POPE at room temperature (T~21 °C, top) and after heating up the system to 40 °C (bottom).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, the membrane curvature has moved into the focus of membrane protein research (Iversen et al, 2015;Tieleman et al, 2021), one prominent example being the exact arrangement of the ATPases in the tubular cristae of mitochondria (Blum et al, 2019) or the mechanosensitive FIGURE 5 | amplitude histogram is shown in e; in total 5 channels were present in the recording. (E), Current amplitude histograms of KcsA channels in pure POPE at room temperature (T~21 °C, top) and after heating up the system to 40 °C (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…Piezo channels (Guo and MacKinnon, 2017). Also coarse-grained simulations of a voltage-gated ion channel, KvAP, suggest deformation of the surrounding membrane (Tieleman et al, 2021). It has been experimentally shown that the curvature leads to a sorting of KvAP channels according to the preferred curvature (Quemeneur et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] In order to improve sampling of lipid-protein interactions, especially in heterogeneous membranes, many MD studies have taken advantage of coarse-grained (CG) representations, e.g., using Martini, a widely used CG method for lipid structures. 40,41 Martini CG simulations of membranes and membrane proteins have contributed significantly to the understanding of how membrane proteins modulate their lipidic environments, both at the distribution and structural levels. 42,43 Here, we have employed an extensive set of MD simulations to characterize the structural effects of prestin on the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In the COGRIMEN method, we employ the MARTINI 17 force field to represent coarse-grained proteins. MARTINI proved to be very effective in studying membrane behavior and lipid–protein interactions, 43 which can be even more accurate in refined MARTINI3. 44 In standard MARTINI, the hydrophobic effect is modeled by having stronger pairwise interactions between similar polar (P-type) and apolar (C-type) bead types compared to their cross interactions.…”
Section: Introductionmentioning
confidence: 99%